Strengthening the role of science and technology in disaster risk reduction: the Chilean strategy. Issue 1 (11th October 2022) - Gil, Magdalena; Rivera, Felipe
Abstract : This paper presents an integrative case study of Chile's national strategy of research, development, and innovation (R&D+i) for disaster resilience and progress towards developing the institutional conditions necessary for its successful implementation. The paper covers the period between 2016 and 2021, concentrating on the work of the Chilean Commission of R&D+i for Resilience to Disasters of Natural Origin (CREDEN). Through an analysis of the official records of the initiative at all of its stages, and 29 semi‐structured interviews with CREDEN members and stakeholders, we aim to present a successful example of strengthening the role of science and technology in disaster risk reduction. Chile's experience is particularly interesting because its strategy focused on R&D+i and proposed developing an industry of scientific‐based technological solutions for disaster resilience. The study also illustrates how strategic interaction between academia, state, and industry can be a key factor in aligning knowledge production to tackle current socio‐technical challenges. نبذة مختصرة: تقدم هذه الورقة دراسة حالة متكاملة لدراسة استراتيجية شيلي الوطنية للبحث والتطوير والابتكار (R & D + i) من أجل القدرة على الصمود في مواجهة الكوارث والتقدم نحو تطوير الظروف المؤسسية لتنفيذها بنجاح. يغطي المقال الفترة بين 2016‐2021 ، مع التركيز على عمل اللجنة التشيلية للبحث والتطوير والابتكار لمقاومة الكوارث للمخاطر الطبيعية. من خلال تحليل السجلات الرسمية للمبادرة في جميع مراحلها و 29 مقابلة شبه منظمة مع أعضاء اللجنة التشيلية للبحث والتطوير والابتكار لمقاومة الكوارث للمخاطر الطبيعية و الأطراف الفاعلة، نهدف إلى إظهار حالة ناجحة لتعزيز دور العلم والتكنولوجيا في الحد من مخاطر الكوارث. تعد التجربة التشيلية مثيرة للاهتمام بشكل خاص لأن الاستراتيجية ركزت على دور البحث والتطوير والابتكار واقترحت تطوير صناعة الحلول التكنولوجية القائمة على العلم لمقاومة الكوارث. توضح دراسة الحالة أيضًا كيف يمكن أن يكون التفاعل الاستراتيجي بين الأوساط الأكاديمية, الدولة والصناعة عاملاً رئيسيًا لمواءمة إنتاج المعرفة و لمعالجة التحديات الاجتماعية والتقنية الحالية. الكلمات الدالة: الأوساط الأكاديمية ، دراسة الحالة ، مخاطر الكوارث ، السياسة العامة ، العلو 摘要: 本文介绍了智利国家抗灾研究、发展和创新战略 (R&D+i) 的综合案例研究，以及为成功实施制定制度条件的进展。本文涵盖2016年至2021年，重点介绍智利R&D+i委员会在对抗自然灾害方面的工作。通过对该倡议各个阶段的官方记录进行分析，并对CREDEN成员和利益相关者的29次半结构化访谈进行分析，我们希望展示科学技术在减少灾害风险中重要性作用的成功案例。智利的经验特别有趣，因为该战略侧重于R&D+i的作用，并提议发展以科学为基础的抗灾技术解决方案产业。该案例研究还说明了学术界、国家和工业界之间的战略互动并如何成为协调知识创造的关键因素，以应对当前的社会技术挑战。 关键词：学术界，案例研究，灾难风险，公共政策，科学